Nighttime Calls, Pages, and Interruptions to the On-Call Surgery Resident. Issue 6 (June 2022) - Parrado, Raphael H.; Notrica, David M; Molitor, Mark S.
Background: Communication is a keystone to good medical practice. At night, as physician numbers decrease, frequent, nonurgent interruptions have shown to disrupt patient care and impact resident/physician wellness. Potentially, interruptions can lead to an increase in medical errors. The frequency and activities interrupted during night calls have not been fully described. Methods: For a period of 44 days (August through September), all calls and pages received during the 12-hour night call session were documented. Calls were analyzed by caller, urgency, need for intervention, and resident interrupted by the communication. Results: A total of 494 communications were identified with a mean of 10 calls per shift (IQR 7-14). Communications lasted a mean of 2.7 +/− 2.9 minutes. Direct calls occurred in 78% and pages in 22% of the cases. From the non-ED calls (n = 335), most of them came from nursing staff (85%), followed by other specialties (12%). Five percent of the calls were directed to the wrong service. Communications occurred during charting (41%), patient assessment (33%), interrupted resident's sleep (12%), or during a surgical procedure (6%). Communication required no action in 47% of the cases. A physician order was needed in 41%, while bedside clinical assessment was required in 12% of the calls. Conclusions: Communications are common at night, but most did not require clinical assessment. A large portion of communications interrupted direct patient care. An opportunity exists to eliminate nonproductive communications and improve the quality of medical education.